Exploring Students' Motivation in Online English Learning during the COVID-19 Pandemic: A Case Study of Eighth-Grade Students at MTsN 2 Palu - Widya Hastuti, Sri Reski; Nurdin, Nurdin; Afifah, Afifah (English Tadris Department, Tarbiyah and Teacher Training Faculty, Datokarama State Islamic University Palu, 2023)
Education has become a new challenge in Indonesia during the covid-19 pandemic because of many changes that occurred in the education system, either in the learning methods or the learning strategies which finally affects the learning motivation of the students. This research aims to explain in detail how the objective conditions of motivation experienced by the students in online learning English and what factors affect the students’ learning motivation in online learning English during the covid-19 pandemic. The research question of this research was, “How is the eighth grade students’ motivation in learning English at MTsN 2 Palu during the covid-19 pandemic?” This research was conducted with a qualitative descriptive approach. The participants involved in this research were 1 teacher and 82 students in MTsN 2 Palu. Data collection techniques used by the researcher were interview and documentation techniques. The validity of the data was done by the triangulation method. The analysis technique applied refers to Miles and Huberman's interactive data inductive model, which includes data reduction, data presentation, and drawing conclusions or verification. The results of this research shows that some students were adequately motivated and some students had low motivation during the online learning. This can be seen directly from the results of this research through interviews and documentation to respondents. Moreover, the factors that influence the students’ learning motivation during the pandemic are students’ learning enthusiasm, family economic problems, and the lack of connection with the students’ parents.